Bosentan regulates the expression of adhesion molecules on circulating T cells and serum soluble adhesion molecules in systemic sclerosis-associated pulmonary arterial hypertension. Issue 8 (20th November 2007) - Iannone, F; Riccardi, M T; Guiducci, S; Bizzoca, R; Cinelli, M; Matucci-Cerinic, M; Lapadula, G
Abstract : Objectives: To study the expression of adhesion molecules in patients with systemic sclerosis (SSc) with and without pulmonary arterial hypertension (PAH) and the effects of therapy with the endothelin-1 (ET-1) receptor antagonist, bosentan. Methods: In all, 35 patients with SSc and 25 healthy donors (HD) were selected for this study. Of 35 patients, 10 had isolated PAH assessed by Doppler echocardiography and treated with bosentan. Peripheral blood (PB) lymphocytes were isolated by density gradient centrifugation, and the expression of lymphocyte function-associated antigen-1 (LFA-1), very late antigen-4 (VLA-4) and L-selectin on CD3 T cells was assessed by double immunofluorescence and flow-cytometry. As endothelial activation markers, serum soluble P-selectin, platelet/endothelial cell adhesion molecule (PECAM)-1, vascular cell adhesion molecule (VCAM)-1, intercellular adhesion molecule (ICAM)-1 and von Willebrand factor (vWF) antigen were assessed by ELISA. In patients with SSc-PAH, T cell subsets and soluble endothelial markers were assessed at baseline and after 6 and 12 months of bosentan therapy. Results: In patients with SSc-PAH, serum soluble ICAM-1, VCAM-1, P-selectin and PECAM-1 levels were higher than in HD at baseline and fell to normal values after 12 months of bosentan therapy. CD3–LFA1 T cells were significantly higher in PAH-SSc at baseline than in HD or SSc and significantly decreased after therapy. CD3–L-selectin T cells were significantly lower in SSc-PAH at baseline than in HD or SSc and rose to normal levels after bosentan therapy. Conclusions: This study confirms that endothelial activation occurs in SSc, and suggests that changes in the T cell/endothelium interplay take place in SSc-associated PAH. Bosentan seems to be able to hamper these changes and restore T cell functions in these patients.